Calculation method of external fault short-circuit current for variable-speed pumped storage units based on time-domain dynamic circuit - He, Rufei; Lu, Qinghui; Ma, Yiming; Qiao, Jian; Li, Yongqi; Peng, Yumin; Yin, Xianggen; Li, Yao (Frontiers in Energy Research, 2023)
The calculation method of external fault short-circuit current of large units with clear mechanisms and practicality is of great value in engineering practice. Due to the special AC excitation structure and control mode, the external fault short-circuit characteristics of variable speed pumped storage units (VSPSU) are greatly different from those of conventional units. Therefore, this paper proposes a calculation method for external fault short-circuit current based on time-domain dynamic circuit. According to the excitation and control characteristics of VSPSU under external fault, the VSPSU under external fault is divided into two cases: continuous excitation and jumper action. Based on space vector analysis, the time-domain dynamic circuit models are established respectively. On this basis, the analytical formula of the external fault short-circuit current of VSPSU is derived by combining the transition boundary conditions of the two cases and the dynamic characteristics of the stator flux linkage. Finally, the comparison with PSCAD/EMTDC simulation results shows that the proposed VSPSU external fault short-circuit current calculation method has high accuracy and practical value, which can meet the needs of primary equipment selection and relay protection of variable speed pumped storage power plants.